Notification of Effectiveness of Partial Distribution of the General Reserve Attributed to Windfall Gold Sale Profits. (Policy Papers; Policy Paper, 2012)
On February 24, 2012, the Executive Board approved a partial distribution of the general reserve equivalent to SDR 700 million attributed to part of the gold sales windfall profits to all members in proportion to their quotas.